A theory of reasoned action model: applied science MRSM student's attitude towards accountant as a career / Mohamad Azmi Nias Ahmad - Nias Ahmad, Mohamad Azmi (2003)
Expectancy theory serves as a theoretical foundation for many studies to understand the factors that affect the students to choose or to reject any career. This model would easily identify the respondent's desired accounting career outcome, their believed on the attractiveness of the outcome and their effort they willing to spend in order to be an accountant. The finding was in contrary with the theory. The attitude between students who choose accountancy career and students who did not choose accountancy career were similar because they are exposed to the same information as they in the same streams.